Understanding civic education in Hong Kong: a Bernsteinian approach. Issue 4 (4th July 2021) - Yan, Kin Cheung Adrian
ABSTRACT: This paper draws on Basil Bernstein's theory of pedagogic discourse and practice to explain the controversy surrounding civic education in Hong Kong, through the case of a compulsory secondary school subject called Liberal Studies (LS). The distinct advantage of a Bernsteinian approach is that its conceptual grammar cogently captures the contentious nature of LS and locates the structural autonomy of teachers. This article highlights the fragmented nature of the LS curriculum, which attests to a historical legacy of the Hong Kong education system that favours a subject-based curriculum in practice and a managerialist approach to teacher staffing. These institutional parameters exert profound influences on LS teachers' modalities of practice. This study contributes to the burgeoning interest in applying Bernsteinian scholarship to the East-Asian region by nuancing the role of teachers in mediating the contentious LS curriculum and implementing civic education. Finally, further application of the Bernsteinian approach will be discussed.